Two dielectric anomalies and impedances of the x CoFe2O4 - (1-x) Bi3.15Nd0.85Ti3O12 (x = 0, 0.3, 0.5) ceramics with coherent interfaces. (1st July 2017) - Zhang, Hongjun; Ke, Hua; Zeng, Gang; Jia, Dechang; Zhou, Yu
Abstract: Two temperature dependence dielectric anomalies are observed in the series of CoFe2 O4 (CFO)/Bi3.15 Nd0.85 Ti3 O12 (BNdT) composite ceramics arising from a periodic structural fluctuation found by high resolution transmission electron microscopy (HRTEM) in the BNdT phase. The latter dielectric anomaly upshifts from 580 °C to 760 °C with the increasing of CFO contents. Higher Curie temperatures are attributed to the larger orthorhombicity values with the effects of the different thermal expansion coefficients and the coherent interfaces between BNdT and CFO. The conductive mechanisms stemming from grain boundaries and plate boundaries were merged into one process approximately for proper CFO contents. Graphical abstract: